2014
DOI: 10.1002/dta.1731
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cannabimimetic agents metabolized by carboxylesterases

Abstract: Synthetic cannabimimetic agents are a large group of diverse compounds which act as agonists at cannabinoid receptors. Since 2004, synthetic cannabinoids have been used recreationally, although several of the compounds have been shown to cause severe toxicity in humans. In this study, the metabolism of two indazole carboxamide derivatives, AB-PINACA and AB-FUBINACA, was investigated by using human liver microsomes (HLM). For both compounds, a major metabolic pathway was the enzymatic hydrolysis of the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
106
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(126 citation statements)
references
References 47 publications
18
106
0
2
Order By: Relevance
“…Terminal carboxamide hydrolysis, a reaction predominantly catalyzed by carboxylesterase 1 (29), yielded the most intense AB-PINACA metabolite at 1 and 3 h, AB-PINACA carboxylic acid (A23), with an absolute MS peak area 10 times higher than the second most intense metabolite A8 (Fig. 1a).…”
Section: Metabolites Generated By Carboxamide Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal carboxamide hydrolysis, a reaction predominantly catalyzed by carboxylesterase 1 (29), yielded the most intense AB-PINACA metabolite at 1 and 3 h, AB-PINACA carboxylic acid (A23), with an absolute MS peak area 10 times higher than the second most intense metabolite A8 (Fig. 1a).…”
Section: Metabolites Generated By Carboxamide Hydrolysismentioning
confidence: 99%
“…Takayama et al incubated AB-PINACA with HLM and identified three hydroxylated metabolites (28), while Thomsen et al identified 10 metabolites in HLM, with AB-PINACA carboxylic acid as the major metabolite. The latter also identified carboxylesterase 1 (CES1) as the key enzyme for amide hydrolysis (29). No 5F-AB-PINACA metabolism data are available.…”
Section: Introductionmentioning
confidence: 99%
“…Major metabolites were identified which included monohydroxylated, dihydroxylated, trihydroxylated, and mono-and dihydroxylated glucuronide conjugates, and dihydroxylated with ketone formation at the N-pentyl side chain. 26 Thomsen et al 27 studied the metabolism of two indazole carboxamide derivatives, AB-PINACA and AB-FUBINACA, by incubation with human liver microsomes (HLM), and human pulmonary microsomes (HPM). The major metabolites were the carboxylic acid derivatives of both synthetic cannabinoids.…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
“…Moreover, Takayama et al [2014] incubated several substrates including AB‐FUBINACA with human liver microsomes, which yielded one mono‐hydroxylated metabolite. Thomsen et al [2015] did the similar experiment incubated several substrates including AB‐FUBINACA with human liver microsomes. The discovered that using AB‐FUBINACA substrate yield three product ions at m/z 109, 253, and 324; these are mono‐ and di‐ hydroxylation derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no specific references to the name AB‐FUBINACA, the patent describes 523 analogues with C 20 H 21 FN 4 O 2 references to AB‐FUBINACA as “Example 2”. In vitro data shows that this compound is a very potent ligand for the cannabinoid (CB1) receptor, with a binding constant of 0.9 nM and an EC 50 of 23.2 nM for receptor activation as measured by GTPγS hydrolysis [Thomsen et al, 2015]. By 2012, AB‐FUBINACA was found in blended herbal products in Japan, Europe, and the United States.…”
mentioning
confidence: 99%